Effect of implant crestal position on primary stability before and after loading: an in vitro study - Jessica Pires de CARVALHO; Umberto Demoner RAMOS; Luiz Gustavo de SOUSA; Paulo Batista de VASCONCELOS; Michel Reis MESSORA; Daniela Bazan PALIOTO; Sérgio Luis Scombatti de SOUZA (Universidade Estadual Paulista, 2022)
Abstract Introduction Primary stability is one of the goals of modern implant dentistry and if achieved, reduces treatment time for prosthetic rehabilitation and the number of interventions made in patients mouth. Several companies state as protocol for connical conection implants, a subcrestally positioning. Objective This in vitro study aimed to evaluate the effect of placing a conical connection implant equicrestally and subcrestally on static and loading condition in two types of bone density. Material and method A total of 200 bone cylinders were extracted from femur of pigs, standardized by means of x-rays and computerized microtomography scan (microCT) and separated in low and high density specimens. The implants were placed on the center of the bone cylinders and were evaluated before and after loading by means of microCT and histomorphometry. Result The results showed that placing the evaluated implant subcrestally provided better primary stability and performance on static and loading situations on low and high density bone. Conclusion Placing implant subcrestally improve primary stability outcomes under loading and static situations.